Effect of Gentamicin Therapy on Auditory Brainstem Evoked Response in Full Term Infant - Nagat Belkasem; Arij Abdelgader (AlQalam Journal of Medical and Applied Sciences, 2024)
Gentamicin, an aminoglycoside antibiotic widely used in neonatal nurseries and intensive care units for treating neonatal sepsis, is known to have nephrotoxicity and ototoxicity. The evaluation of the ototoxicity can be achieved through auditory brainstem response, which is recommended in neonatal screening programs. This study aimed to evaluate the effect of gentamicin on auditory brainstem response in term neonates. A cross-sectional prospective study was conducted on 42 term neonates who received gentamicin for the treatment of neonatal sepsis, along with 30 normal neonates as controls. Auditory brainstem response tests were performed on all neonates after one month. There was a statistically significant prolongation of latency in wave I at intensities of 90dB and 70dB. Prolongation was also observed in waves III and V, although it was not statistically significant. There was no statistically significant difference between the two groups in terms of interpeak latency I-III, III-V, and I-V. The delay in wave I latency suggests distal auditory nerve affection in term neonates who received gentamicin at regular therapeutic doses. The authors recommend the use of auditory brainstem response for monitoring gentamicin usage in neonatal units. الجنتاميسين هو مضاد حيوي من مجموعة الامينوجليكوسيدات تستخدم بشكل شائع لعلاج حالات التسمم لدى الأطفال حديثي الولادة. كما له سميه كلوية وسميه سمعية للأطفال حديثي الولادة يمكن تقييم السميه السمعية من خلال استجابة الجذع السمعي للدماغ والذي يوصى بيه في برامج المسح السمعي لحديثي الولادة. تهدف هذه الدراسة إلى تقييم مدى تأثير دواء الجنتاميسين على منعكس جذع المخ السمعي لدى الأطفال حديثي الولادة. تضمنت هذه الدراسة عدد 72 طفلا من حديثي الولادة 42منهم ممن عولجوا بدواء الجنتاميسين كدواء علاجي لتسمم الدم و30 آخرون كمجموعة ضابطة حيث اجري لهم جميعا قياس منعكس جذع المخ السمعي بعد فترة شهر من تاريخ الولادة.أظهرت هذه الدراسة وجود فرقات إحصائية واضحة بين المجموعتين في مدى تأخر الموجة الأولى عند درجتي 70و90 ديسبلو كما وجد تأخر موجي عند الموجة الثالثة والخامسة ولكن ليس ذا أهميه إحصائية كما وجد عد عدم اختلاف إحصائي في المسافة بين الموجات الأولى والثالثة ,الثالثة و الخامسة, الأولى والخامسة. تأخر الموجة الأولى يبين مدى تأثر الجهة البعيدة العصب السمعي جراء تأثير دواء الجنتاميسين لدى الأطفال الرضع ,كما يجب التوصية باستخدام فحص المنعكس لجذع المخ السمعي للأطفال الذين يخضعون لعلاج الجنتاميسين